Development of Arginine-Containing Well-Defined Polymers - Taykoz, Damla; Bulmuş Zareie, Volga (Izmir Institute of Technology, 2014)
The aim of this work is to synthesize arginine-containing well-defined polymers via reversible addition-fragmentation chain transfer (RAFT) polymerization and perform preliminary investigation on the use of these polymers in nucleic acid complexation for potential gene therapy applications. Pentafluorophenyl methacrylate (PFMA) was chosen as an active ester monomer to produce polymers having functional groups available for further modification. RAFT polymerization of PFMA was performed varying polymerization conditions such as feed composition and polymerization temperature. Polymers (PPFMA) were characterized using nuclear magnetic resonance (NMR) spectroscopy and gel permeation chromatography. Linear increase in ln[M]0/[M] with polymerization time, and number average molecular weight (Mn) with monomer conversion indicated RAFT controlled polymerization of PFMA under the conditions tested. Furthermore, block copolymers of PFMA with poly(ethylene glycol) methacrylate (PEGMA) as a biocompatible component were prepared. Copolymerization was studied using both P(PFMA) and P(PEGMA) as macro RAFT agent. Copolymerization kinetic studies indicated that chain extension block copolymerizations were successfully performed using both macroRAFT agents. P(PFMA) was reacted with arginine methylester (AME) in the presence of triethylamine (TEA). 100% of P(PFMA) active ester groups could be modified with AME at a polymer/AME/TEA mole ratio of 1/1/3, as determined by 1H-NMR spectroscopy. The AME modified polymers were complexed with a 681-bp DNA fragment through electrostatic interactions at varying nitrogen/phosphate (N/P) ratios. Gel electrophoresis experiments revealed that AME-modified P(PFMA) was able to complex with DNA at a N/P ratio of 200. Furthermore, the hydrodynamic diameter (Dh) of polymer/DNA complexes in phosphate buffer saline was found to be 58 nm, while the free DNA displayed a Dh of 109 nm, indicating the complexation of DNA by AME-modified P(PFMA).
Arjinin İçeren İyi Tanımlanmış Polimerlerin Geliştirilmesi
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2014
Includes bibliographical references (leaves: 40-42)
Text in English; Abstract: Turkish and English
Full text release delayed at author's request until 2017.08.11
Keywords: Pentafluorophenyl methacrylate; Reversible addition-fragmentation chain transfer; Polymers; Polymerization